2017
DOI: 10.1103/physrevlett.119.257001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Induced Superconductivity in Ultrathin Pb Films with Magnetic Impurities

Abstract: It is well known that external magnetic fields and magnetic moments of impurities both suppress superconductivity. Here, we demonstrate that their combined effect enhances the superconductivity of a few atomic layer thick Pb films grown on a cleaved GaAs(110) surface. A Ce-doped film, where superconductivity is totally suppressed at a zero field, actually turns superconducting when an external magnetic field is applied parallel to the conducting plane. For films with Mn adatoms, the screening of the magnetic m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In general, the application of a sufficiently strong magnetic field destroys the superconducting state in a superconductor because of the Zeeman effect, which breaks the paired electrons in a spin-singlet state, and the orbital effect, where the vortices penetrating into the superconductors annihilate the energy gain from creating the paired electrons. However, the study of the interplay of superconductivity and magnetism in the recent past has experimentally observed that a high magnetic field can also induce superconductivity in a number of materials at low temperatures [31,[145][146][147][148][149][150].…”
Section: Condensed-matter Counterpart: Magnetic-field-induced Superco...mentioning
confidence: 99%
“…In general, the application of a sufficiently strong magnetic field destroys the superconducting state in a superconductor because of the Zeeman effect, which breaks the paired electrons in a spin-singlet state, and the orbital effect, where the vortices penetrating into the superconductors annihilate the energy gain from creating the paired electrons. However, the study of the interplay of superconductivity and magnetism in the recent past has experimentally observed that a high magnetic field can also induce superconductivity in a number of materials at low temperatures [31,[145][146][147][148][149][150].…”
Section: Condensed-matter Counterpart: Magnetic-field-induced Superco...mentioning
confidence: 99%
“…The problem of magnetic impurities in metallic superconductor hosts has been of great interest for a long time [1][2][3][4][5]. Understanding interactions among magnetic impurities in such hosts poses important questions at the interface of fundamental and applied sciences [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Magnetic impurities are generally thought to suppress superconductivity; however, the actual pair breaking process can be dominated by different mechanisms.…”
Section: Introductionmentioning
confidence: 99%